KONSEP KERUKUNAN DALAM KOMUNIKASI PEMBANGUNAN AGAMA DI SOSIAL MEDIA - Rahmatika, Arina (KOMUNIKE, 2018)
Information and communication technology is growing rapidly in Indonesia and has become part of the community, one of which is social media. The social presence of the media as a public space becomes a new style of communication even in creating inter-religious communication spacesin the community. This certainly will affect the level of harmony among religious people in Indonesia. Through communication of the development of social media as a medium of communication, dissemination, it is hoped that it can build a strengthening of religious harmony through various elements of society, both individual and institutional